Effect of graphene oxide on single fiber pullout behavior. (19th April 2021) - Chindaprasirt, Prinya; Sukontasukkul, Piti; Techaphatthanakon, Apisit; Kongtun, Suriyawan; Ruttanapun, Chesta; Yoo, Doo-Yeol; Tangchirapat, Weerachart; Limkatanyu, Suchart; Banthia, Nemkumar
Highlights: Addition of graphene oxide increases compressive strength of cement mortar. Denser microstructure is observed in graphene mortar as compared to normal mortar. Graphene oxide improves pullout load, bond strength and energy absorption of fiber. Pullout behavior of fiber embedded in GM mortar is sensitive to loading rate. Abstract: The properties of fiber reinforced concrete (FRC) depends strongly on bond between fiber and cement matrix. Any change in matrix and fiber characteristics affects the bond behavior. In this study, the effect of graphene oxide on cement composite strength and bond behavior between fiber and cement matrix was investigated. The graphene oxide solution with concentration of 10 mg/ml was mixed with cement mortar at 0.05% by weight of cement. Four types of fibers viz., hooked end steel, double hooked end steel, polypropylene and glass fibers were tested by embedding in both plain cement mortar (M) and cement graphene mortar (GM). The single fiber pullout test was performed at the rates of 60 and 180 mm/min. Results were collected in form of failure mode, scanning electron microscope (SEM) images, bond-slip response, bond strength and energy absorption. SEM images showed that the failure modes depended on fiber type, matrix type and loading rate. The steel fibers showed almost no damage except for the change of hooked end shape at the fiber end. For polypropylene fiber, the fiber surface scraping was commonly observed while the debonding of coating material was observed for glass fiber. The bond strength was higher in GM mortar than that of M mortar and increased with the increase in loading rate. In the case of fiber type, steel fibers exhibited higher bond and energy absorption than both polypropylene and glass fibers.